Analysis of science process skills and students' creativity in lower class science learning - Dinda Widyastika; Rudi Hermansyah Sitorus; Muhammad Dekar Nasution; Fathiyah Nabila; Salsabilla Salsabilla (Jurnal Scientia, 2024)
This research aims to identify students' science process skills and creativity in low-grade science learning courses. The research method used in this research is descriptive qualitative. The subjects of this research were all 79 semester 3 students of Stambuk 2022. The subject selection technique used was purposive sampling. The data collection technique used is the Miles and Huberman model. The findings of this research are that students' science process skills and creativity are good or not. This is because the assessment of students is known through observation and also creative abilities. Suggestions and recommendations for the future are that it is hoped that the assessment of students' science process skills and creativity will be measured and assessed systematically and using valid assessment instruments. This is done so that it can help evaluate science process skills and creativity so that students can more optimally improve science process skills and creativity.